2021
DOI: 10.3390/ijerph19010063
|View full text |Cite
|
Sign up to set email alerts
|

Links of Perceived Pornography Realism with Sexual Aggression via Sexual Scripts, Sexual Behavior, and Acceptance of Sexual Coercion: A Study with German University Students

Abstract: Exposure to pornographic material has been linked to sexual aggression perpetration and victimization in a large body of research. Based on social learning theory and 3A theory of script learning, this study contributes to this research by testing the hypothesis that the more realistic pornography is perceived to be by young adults, the more likely they are to experience and engage in sexual aggression. Two underlying pathways were proposed: one path via scripts and patterns of sexual behavior regarding consen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…In our study, active porn watching was significantly associated with higher sexual-related knowledge ( Table S2 ). However, evidence also shows that the presence of abuse, assault, and sexual exploitation in porn videos increases the risk of sexual coercion and harmful, gender-stereotypical attitudes [ 32 , 37 , 38 ]. Nowadays, pornographic culture has a tendency to transform into “pornographification of popular culture,” and soft pornography is mixed with entertainment products [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, active porn watching was significantly associated with higher sexual-related knowledge ( Table S2 ). However, evidence also shows that the presence of abuse, assault, and sexual exploitation in porn videos increases the risk of sexual coercion and harmful, gender-stereotypical attitudes [ 32 , 37 , 38 ]. Nowadays, pornographic culture has a tendency to transform into “pornographification of popular culture,” and soft pornography is mixed with entertainment products [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…the diversity of conceptions regarding its limits, it can be considered that the age group of young adults encompasses all individuals aged between 18 and 35 years (e.g., Krahé et al, 2022). This developmental stage is characterized by late adolescence and entry into adulthood (Erikson, 1963).…”
Section: Notwithstandingmentioning
confidence: 99%
“…It has also been suggested that scripting effects may be more likely among those who perceive pornography to be realistic in its depiction of sexuality and less likely among those who do not [1,[3][4][5]. This may be because media perceived as realistic is more likely to be attended to and imitated [1,3].…”
Section: Introductionmentioning
confidence: 99%